Physiology and Pathophysiology of ClC-K/barttin Channels - Fahlke, Christoph; Fischer, Martin (Frontiers in Physiology, 2010)
ClC-K channels form a subgroup of anion channels within the ClC family of anion transport proteins. They are expressed predominantly in the kidney and in the inner ear, and are necessary for NaCl resorption in the loop of Henle and for K+ secretion by the stria vascularis. Subcellular distribution as well as the function of these channels are tightly regulated by an accessory subunit, barttin. Barttin improves the stability of ClC-K channel protein, stimulates the exit from the endoplasmic reticulum and insertion into the plasma membrane and changes its function by modifying voltage-dependent gating processes. The importance of ClC-K/barttin channels is highlighted by several genetic diseases. Dysfunctions of ClC-K channels result in Bartter syndrome, an inherited human condition characterized by impaired urinary concentration. Mutations in the gene encoding barttin, BSND, affect the urinary concentration as well as the sensory function of the inner ear. Surprisingly, there is one BSND mutation that causes deafness without affecting renal function, indicating that kidney function tolerates a reduction of anion channel activity that is not sufficient to support normal signal transduction in inner hair cells. This review summarizes recent work on molecular mechanisms, physiology and pathophysiology of ClC-K/barttin channels.